2013
DOI: 10.1590/0037-8682-0063-2013
|View full text |Cite
|
Sign up to set email alerts
|

Larvicidal effects of endophytic and basidiomycete fungus extracts on Aedes and Anopheles larvae (Diptera, Culicidae)

Abstract: Introduction:In vitro bioassays were performed to access the larvicidal activity of crude extracts from the endophytic fungus Pestalotiopsis virgulata (Melanconiales, Amphisphaeriaceae) and the saprophytic fungus Pycnoporus sanguineus (Basidiomycetes, Polyporaceae) against the mosquitoes Aedes aegypti and Anopheles nuneztovari. Methods: The extracts were tested at concentrations of 100, 200, 300, 400 and 500ppm. Ethyl acetate mycelia (EAM) extracts and liquid culture media (LCM) from Pe. virgulata and Py. sang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 27 publications
0
10
2
Order By: Relevance
“…Bramachary and Paily, 23 reported metabolite products similar to enzime chitinase as produced by Pseudomonas fluorescens has LC 50 values of 2.29 ug/mL or 2.29 ppm against larvae of Culex quinquefasciatus. However, the LC 50 value of natural larvacide formula used in this study was lower if compared to Bucker et al, 24 study which reported that endophytic fungi extract and basidiomiset extract indicate LC 50 values at101.8 ppm and 156.8 ppm against Aedes aegypti larvae. In addition, the mixture of LC 50 Beauveria bassiana crude metabolites and enzyme chitinase is also lower than in study by Widastuti, 9 stating that LC 50 value of isolate BKUd01 against Aedes aegypti was achieved at concentration 2000 ppm.…”
Section: Resultscontrasting
confidence: 72%
“…Bramachary and Paily, 23 reported metabolite products similar to enzime chitinase as produced by Pseudomonas fluorescens has LC 50 values of 2.29 ug/mL or 2.29 ppm against larvae of Culex quinquefasciatus. However, the LC 50 value of natural larvacide formula used in this study was lower if compared to Bucker et al, 24 study which reported that endophytic fungi extract and basidiomiset extract indicate LC 50 values at101.8 ppm and 156.8 ppm against Aedes aegypti larvae. In addition, the mixture of LC 50 Beauveria bassiana crude metabolites and enzyme chitinase is also lower than in study by Widastuti, 9 stating that LC 50 value of isolate BKUd01 against Aedes aegypti was achieved at concentration 2000 ppm.…”
Section: Resultscontrasting
confidence: 72%
“…(Linnaeus, 1758) (Polyporales, Polyporaceae) and Pestal otiopsis sp. Steyaert, 1949 (Xylariales, Amphisphaeriaceae) against the ye llow fever mosquito, Aedes aegypti (Linnaeus, 1762) (Diptera, Culicidae), as observed by Bucker (7) . The observed differences could be related to species-specifi c differences or to the methods of extraction, as the author observed different impacts according to tested formulations.…”
mentioning
confidence: 89%
“…However, although there are few studies that investigate the use of fungi as a control measure, some fungal species have shown promising results against insects (6) (7) .…”
mentioning
confidence: 99%
“…Most alkaloids have strong physiological effects in animals even at low doses so have psychoactive, medicinal and pharmaceutical applications. It has been reported that of the pigments of Pycnoporus strains; cinnabarin, cinnabarinic acid and tramesanguin are the main components, and act as antioxidants, free radical scavengers, antifungals (Borderes et al 2011), anticarcinogens (Smânia et al 2003), are immunomodulatory, larvicidal (Bücker et al 2013), have lechmanicidal activity (Correa et al 2006) and antiviral, antibacterial (Smânia et al 1995(Smânia et al , 2003 and anti-inflammatory activity (Kuanget et al 2010). Pigment characterization, and its biosynthesis have been described by several authors.…”
Section: Medical and Pharmaceuticalmentioning
confidence: 99%